Aortic pulse wave velocity measurement in systemic sclerosis patients - M. Sebastiani; F. Coppi; A. Manfredi; D. Giuggioli; M. Colaci; R. Rossi; C. Ferri (PAGEPress Publications, 2012)
Background. Systemic sclerosis (SSc) is characterized by endothelial dysfunction and widespread microangiopathy. However, a macrovascular damage could be also associated. Aortic pulse wave velocity (aPWV) is known to be a reliable indicator of arterial stiffness and a useful prognostic predictor of cardiovascular events. Moreover, aPWV may be easily measured by non-invasive, user-friendly tool. Aim of our study was to evaluate aPWV alterations in a series of SSc patients. Methods. The aPWV was evaluated in 35 consecutive female SSc patients and 26 sex- and age-matched healthy controls. aPWV alterations were correlated with cardiopulmonary involvement. Results. A significant increase of aPWV was observed in SSc patients compared to controls (9.4±3.2 m/s vs 7.3±1 m/s; P=0.002). In particular, 14/35 (40%) SSc patients and only 1/26 (4%) controls (P=0.0009) showed increased aPWV (>9 m/s cut-off value). Moreover, echocardiography evaluation showed an increased prevalence of right atrial and ventricular dilatation (atrial volume: 23.6±6.2 mL vs 20.3±4.3 mL, P=0.026; ventricular diameter 19.5±4.9 mm vs 15.9±1.6 mm; P=0.001) associated to higher values of pulmonary arterial systolic pressure (PAPs) in SSc patients (31.5±10.4 mmHg vs 21.6±2.9 mmHg; P<0.0001; 40% of SSc patients showed an abnormal PAPs). Clinically, SSc patients presented a reduction of six-minute walking test (413±96 m vs 491±49 m; P=0.001), not correlated with pulmonary function tests. Increased aPWV values were evidenced only in SSc patients >50 years old. Furthermore, altered aPWV was more frequently associated with limited cutaneous pattern, longer disease duration (≥5 years), and/or presence of anticentromere antibody (ACA). Conclusions. A significantly higher prevalence of abnormally increased aPWV was evidenced in SSc patients compared to healthy controls. The possibility of more pronounced and diffuse vascular damage in a particular SSc subset (ACA-positive subjects with limited cutaneous scleroderma and longer disease duration) might be raised.